Thailand’s Strategy to Change the Image of Sex Tourism Through Gastro Diplomacy in 2017-2020 - Tholhah, Tholhah; Wafa, Salmaula Nur (Journal of Islamic World and Politics, 2024)
This article aims to determine Thailand's strategy for changing the image of sex tourism through gastrodiplomacy in 2017-2020. The strategy undertaken by Thailand as the nation’s branding started through Global Thai in 2002 and continued through Kitchen of The World in 2003. The program was under the leadership of the Prime Minister of Thailand, Thaksin Shinawatra. Through the ‘Kitchen of the World’ icon, Thailand is expanding its restaurants abroad and becoming an exporter of staples and food ingredient production to various developed and developing countries in the world. The Thai Government’s strategy is a national interest through gastro diplomacy to change the country’s known as sex tourism. That identity echoes Thailand’s strong reputation for culture and travel in Thailand. This article used a qualitative method. Data collection techniques in this research were through reference library studies. The study used constructive perspective, concepts of diplomacy, and gastro-diplomacy as the main focus. The results indicated that Thailand’s strategy in changing the image of sex tourism through gastro diplomacy is through three indicators, namely conducting culinary diplomacy through the World Gourmet Festival and cultural diplomacy through the Songkran Festival as a domestic strategy, as well as branding Thailand through the Kitchen of the World.